The spectrum of GI ischemia 1 - Brandt, Lawrence J. (Henry Stewart Talks, 2022)
Disease incidence and pathophysiology of colon ischemia (CI), Causes and risk factors of CI, Spectrum of CI, Role of colonoscopy, Use of antibiotics